PECULIARITIES OF MICROCIRCULATORY BED VESSEL’S DENSITY CHANGE IN THE LOBULES OF THE WHITE RATS THYMUS IN NORM AND UNDER THE INFLUENCE OF SALTS OF HEAVY METALS WITHIN TWO MONTHS - Dobryanska E. S.; Vatsyk N. S.; Yovbak T. V.; Pitsur D. Yu. (World Science, 2021)
From the three salts of heavy metals consumed by experimental white male rats of reproductive age in low concentrations for 2 months, the least toxic to the body is an aqueous solution of FeSO4 · 7H2O (iron sulphate) at a dose of 0.5 mg / dm3. The most toxic is an aqueous solution of ZnSO4 · 7H2O (zinc salt of sulfuric acid) at a dose of 1,505 mg / dm3, the use of which resulted in an increase in all vessels of the microcirculatory tract in both cortex and medulla of the lobules of thymus compared to the control group. The density of arterioles in the cortex increased 3.3 times, the density of venules - 2 times, the density of capillaries - 1.5 times; in the brain substance there is also a 2-fold increase in the density of arterioles, the density of venules - 1.2 times, the density of capillaries - 2.5 times compared with the control group of animals. In experimental male rats consuming aqueous solutions - CuSO4 · 5H2O at a dose of 0.247 mg / dm3, the density of arterioles and venules in the cortex of the thymus almost did not change, and the density of capillaries, compared with the control group, increased 1.5 times in medulla of thymus, compared with the control group, the density of arterioles increased 1.7 times, the density of venules increased 1.2 times, and the density of capillaries increased 1.6 times.